New-to-Setting Nurse Transitions: A Concept Analysis. Issue 2 (March 2019) - Chicca, Jennifer; Bindon, Susan
Abstract : New graduate nurses transitioning to practice have gained significant attention and dedicated resources. Less obvious are the transitions experienced nurses make to new settings or specialties during their careers. Experienced nurses still need support as they make these adjustments. This article explores the concept of nurse transition and specifically analyzes the concept of new-to-setting nurse transition. Nursing professional development practitioners and others can support experienced nurses through the challenges of new-to-setting transitions.